A novel insecticide seed treatment formulation (Chlorantraniliprole 625 g/L FS) for yellow stem borer and leaf folder management in rice - Patil, Naveenkumar B; Baruah, Aparna; Adak, Totan; G, Basana Gowda; G, Guru Pirasanna Pandi; Annamalai, Mahendiran; S, Raghu; Rath, PC (ORYZA-An International Journal of Rice, 2023)
The potential yield loss of 15-25% rice production is noticed due to different pest infestation in South Asian countries. This is due to the favorable climatic conditions for pests. It compels farmers to use a major chunk of pesticides to prevent/recover from pest attack. Hence, the field experiments were carried out to test the insecticide, Chlorantraniliprole 625 g/L FS as seed treatment formulation. It is evident from the studies undertaken during rabi 2018-19 and kharif 2018, that Chlorantraniliprole provided excellent control over yellow stem borer and leaf folder in conventional variety of rice (CR Dhan 304) and hybrid rice (28P67). Among the different doses, Chlorantraniliprole @ 75.0 g a.i/ha recorded significantly better control registering least dead heart of 5.41, 4.77, 3.43, 2.98% and 2.47% at 14, 21, 28, 35 and 42 days after transplanting, respectively. Similarly for Hybrid (28P67) trial the treatment recorded the least count of leaf folder with 0.57, 0.68, 0.74, 0.81 and 0.89 larvae/hill during the intervals of 14, 21, 28, 35 and 42 days after transplanting, respectively and the highest yield (5.46 t/ha) was registered in treatment which was significantly superior over the other entire dose rates of Chlorantraniliprole and the market standard. Thus, from this study, Chlorantraniliprole @ 75 g a.i /ha can be recommended for controlling stem borer and leaf folder in paddy (both for conventional variety and hybrid).